PENGARUH METODE SQ3R BERBASIS WORDWALL TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN PENDIDIKAN PANCASILA KELAS IV SEKOLAH DASAR - Sita Salsabilla, Safira; Nurwahidin , Muhammad; Abung, Miranda; Erni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem in this research was the low reading comprehension skills of fourth- grade students at UPT SD Negeri 2 Sukoharjo III in Pancasila Education. This study aimed to determine the effect of applying the Wordwall-based SQ3R method on reading comprehension skills. This research used a quantitative with a nonequivalent control group design method. The population consisted of 33 students, and the sample was 33 students, determined by saturated sampling technique. Data were collected using tests and non-tests techniques. Data analysis techniques used simple linear regression tests and independent samples t-test. The results of this study showed an effect of using the Wordwall-based SQ3R method on the reading comprehension skills of fourth-grade students at UPT SD Negeri 2 Sukoharjo III. This study also found a difference in Pancasila Education reading comprehension skills among fourth-grade students at UPT SD Negeri 2 Sukoharjo III for the 2025/2026 academic year compare the treatment using the Wordwall-based SQ3R method and the discussion method. Keywords: reading comprehension skills, SQ3R method